"All I have is myself”: The resilience of international students navigating cultural transitions and support systems in India - Das, Bipasha; Verma, Satyam; Gardia, Alok (Journal of International Students, 2026)
This study employed an embedded mixed-methods exploratory design to investigate international students in India, focusing on resilience, perceived support, and academic adjustment. In the qualitative phase, nine students were interviewed, revealing two main themes: (1) institutional support and peer networks, and (2) resilience through self-reliance. The results revealed that support systems are vital for cultural and academic adjustment. Due to limited access, the students relied on self-reliance, which fostered personal resilience that aided in adaptation. The quantitative phase analyzed the relationship between social support and academic adjustment using data from 180 students, employing mediation analysis. The findings indicated that perceived social support had a positive influence on academic adjustment, whereas duration of stay did not mediate this relationship.